Protecting juvenile defendants in the trial and from the trial: special safeguards in EU and Italian regulations - Zampini, Andrea (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
Both the Directive 2016/800/EU and the Italian national law on juvenile criminal trial (presidential decree no. 448/1988) aim to provide specific safeguards for young suspects and defendants to protect their fragile and still-developing personality, and to ensure that any crime allegedly committed by the minor is an isolated incident in their past. These safeguards are required throughout criminal proceedings, especially during the trial stage, which can be confusing and overwhelming for a juvenile and may seriously impact their development. The trial phase – along with the precautionary limitation of personal freedom – seems to be the most dangerous procedural segment for children’s personalities. The trial is where the justice ‘play’ comes to life on its main stage, with its whole ritual, language, and characters. When attempting to identify safeguards intended to operate during the trial phase, two main fields seem to emerge: one focuses on the issue of assistance, which has to be more profound due to the unique nature of juvenile personality and experience of life; while the other one aims to protect children’s privacy so that their public image will be shielded as much as possible from the negative consequences of the trial. The article first focuses on these aspects by analysing legal regulations and the jurisprudence. In some cases, Italian legal regulation exceeds European directive standards, serving as a model for other legal systems. However, even though the internal regulation formally matches the EU requirement in some instances, it needs further improvement. Also, in terms of the law in action, the Italian jurisprudential approach sometimes weakens the safeguards provided by law, demonstrating the need for different interpretative solutions that are adequate to respect children’s rights fully. In the light of such issues, the author suggests some exegetical solutions.